1960
DOI: 10.1017/s0021859600022449
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding lysine and methionine to the diet of pigs kept on low-protein vegetable foods

Abstract: The beneficial effect on the nutritive value of bread and similar cereals of adding small amounts of lysine and other essential amino acids has recently aroused considerable interest both in Great Britain and in America. Tests carried out with rats have shown considerably improved growth rates accompanied by increased efficiency of food conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1961
1961
1982
1982

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The influence of lysine on daily 1963; ; Robinson, Morgan live-weight gain and feed conversion efficiency at a & . The interpretation of the results of constant crude protein level has been demonstrated many of these experiments is made difficult because in pigs up to 200 lb live weight by Ericson, Larson generally as the level of dietary crude protein & Ostholm (1962) and Evans (1960) Acker, Catron & Hays (1959); t Presentaddress: DepartmentofFarmManagement, McWard et al (1959); and Jones, Livingston & University of New England, Armidale, New South Livingstone (1963). The lack of agreement in the Wales, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of lysine on daily 1963; ; Robinson, Morgan live-weight gain and feed conversion efficiency at a & . The interpretation of the results of constant crude protein level has been demonstrated many of these experiments is made difficult because in pigs up to 200 lb live weight by Ericson, Larson generally as the level of dietary crude protein & Ostholm (1962) and Evans (1960) Acker, Catron & Hays (1959); t Presentaddress: DepartmentofFarmManagement, McWard et al (1959); and Jones, Livingston & University of New England, Armidale, New South Livingstone (1963). The lack of agreement in the Wales, Australia.…”
Section: Introductionmentioning
confidence: 99%
“…T h e importance of the lysine content of the diet is well established and there are many examples in the literature of the improvement in performance that can be brought about by lysine supplementation of diets containing poor-quality proteins (Evans, 1960;Jones, Hepburn, Cadenhead & Boyne, 1962;Rerat & Lougnon, 1965;Ostrowski, 1969). It has also been reported that small improvements in Performance can be obtained when lysine is added to diets containing white fish meal, the protein concentrate most commonly used in this country, but economic appraisal of the results showed that this was not a viable proposition at present prices (Braude & Lerman, 1970).…”
mentioning
confidence: 99%